Characterization of landfill leachate: a case study of a selected landfill in Pahang / Siti Suhaila Harith, Mohd Noor Ramlan and Hafizah Kassim - Harith, Siti Suhaila; Ramlan, Mohd Noor; Kassim, Hafizah (2006)
Domestic solid waste landfill causes major negative environmental impact if not managed in a proper manner. A leachate study was conducted at Batu 55 Landfill in Maran. Leachate were analyzed for physical characteristics such as colour and TSS; biological characteristics such as total cell count, viable count, total coliforms and fecal coliform, and chemical characteristics such as COD, BOD, pH, phosphate, NH3-N, NO3-N, N02r-N, sulphate and heavy metals. Taking into account the low concentration of heavy metals, the low value of the BOD5/COD ratio [(155/9875) < 0.5] and the high contents of NH3-H (629 to 6250 mg.1-1), the leachate was classified as "old' and non-biodegradable. The pH of the leachate from the landfill has basic character (pH ranged between 7.44 to 8.22). Fecal coliform have been detected ranging from 0% to 38.6% of viable count. This is alarming due to the risk of pathogen contamination to ground water. Therefore, establishing appropriate treatment methods is necessary to reduce the pollution intensity.